Energy security and carbon emissions: the role of economic freedom - Cong, Shufeng; Lee, Chin; Li, Chuanhua (Springer Science and Business Media, 2025)
This paper explores the impact of energy security on carbon emissions and analyses the mediating role of different dimensions of economic freedom in this relationship. By examining the mechanisms through which economic freedom can enhance energy security, this study aims to contribute to the formulation of policies that support both economic growth and environmental stewardship in a low-carbon future. The study is based on panel data for 69 countries from 2012-2018, employing the fixed effects model as the main methodology. Results indicate that energy security significantly reduces carbon emissions. Additionally, a comprehensive analysis of six dimensions of economic freedom—business, monetary, trade, investment, and financial freedom—reveals significant mediation effects, while labour freedom shows no significant impact. This study advocates for policies that promote sustainable development and a low-carbon economy. Key recommendations include enhancing energy security through clean energy and efficiency; guiding economic growth towards low-carbon industries; conserving forests; attracting green FDI; enforcing cleaner industrial practices; expanding carbon markets; and promoting economic freedom by streamlining bureaucratic processes.